To solve the equation for y, we need to isolate y on one side of the equation.
Given the equation: 2x - 5y = 17
First, subtract 2x from both sides of the equation to get: -5y = -2x + 17
Next, divide both sides of the equation by -5 to solve for y: y = (-2x + 17)/-5
So the equation for y is y = (-2x + 17)/-5.
To find the value of y for each value of x, substitute the given x-values into the equation for y.
For x = -2:
y = (-2(-2) + 17)/-5
y = (4 + 17)/-5
y = 21/-5
y = -4.2
For x = 0:
y = (-2(0) + 17)/-5
y = (0 + 17)/-5
y = 17/-5
y = -3.4
For x = 2:
y = (-2(2) + 17)/-5
y = (-4 + 17)/-5
y = 13/-5
y = -2.6
So the values of y for each value of x are:
For x = -2, y = -4.2
For x = 0, y = -3.4
For x = 2, y = -2.6
solve the equation for y. Then find the value of y for each value of x. 2x - 5y = 17; x = -2, 0, 2 Solve the equation for y.
1 answer